Bioactive Anti‐Thrombotic Modification of Decellularized Matrix for Vascular Applications. Issue 12 (13th April 2016) - Glynn, Jeremy J.; Hinds, Monica T.
Abstract : The decellularized matrix derived from porcine small intestinal submucosa (SIS) is a widely used biomaterial being investigated for numerous applications. Currently, thrombus deposition and neointimal hyperplasia have limited the use of SIS in some vascular applications. To limit these detrimental processes, this work applies bioactive, endothelial‐inspired properties to the material. SIS is modified with the endothelial cell membrane protein thrombomodulin and the glycosaminoglycan heparin to facilitate protein C activation and anticoagulant activity, respectively. Modifying SIS with thrombomodulin alone enables robust activated protein C (APC) generation, and thrombomodulin activity is maintained after prolonged exposure to fluid shear and blood plasma. Heparin‐modified SIS has a potent anticoagulant activity. When both modifications are applied sequentially, SIS modified first with thrombomodulin then with heparin retains the full activity of each individual modification. Tubular SIS devices are connected to a baboon arteriovenous shunt to quantify thrombus deposition on these materials. After being exposed to flowing whole blood for 60 min, SIS devices modified first with thrombomodulin then with heparin have significantly less platelet accumulation compared to unmodified SIS devices. These studies demonstrate that modifying SIS with thrombomodulin and heparin confers APC generation and anticoagulant activity that results in reduced thrombogenesis. Abstract : The decellularized biomaterial derived from porcine small intestinal submucosa (SIS) is widely used in tissue repair, but can cause blood clot formation. An endothelial‐inspired, biologically active coating consisting of thrombomodulin and heparin inhibits blood coagulation and reduces blood clot formation on SIS when exposed to flowing whole blood in an extracorporeal blood loop, as shown.